DER MUSIKALISCHE SPRACHE DES KOMPONISTEN PIERRE VILLETTE IN DEN „A CAPPELLA MOTETTEN HYMNE A LA VIERGE (OP. 24) UND PANIS ANGELICUS (OP. 80)“ - Miklós FEKETE (Studia Universitatis Babeş-Bolyai. Musica)
This paper presents first of all the importance of the 20th century French composer Pierre Villette, who’s instrumental, vocal-instrumental and choral works are relatively unknown even between musicians. Secondly, this writing focuses on the choral music of the composer, presenting the result of the analysis of the two chosen a cappella motets mentioned in the title (written by Villette in two different periods of his creation). The musical analysis proposes to identify and exemplify a few procedures, compositional techniques of Villette, which – on the one hand – do define the structure, the melodic and harmonic aspects of the musical discourse, and – on the other hand – aim to express the religious belief of the composer.